2022
DOI: 10.1002/ejoc.202200579
|View full text |Cite
|
Sign up to set email alerts
|

α‐Ketobutyrate Production under Continuous‐Flow Conditions Catalyzed by Immobilized L‐Methionine γ‐Lyase

Abstract: l-Methionine γ-lyase (MGL) is a PLP-dependent enzyme which catalyzes the α, γ-elimination reaction in sulfur containing amino acids, such as L-methionine and L-cysteine. Its major applications are on metabolic restriction of methionine to cancer cells, food industry (cheese flavor) and for the synthesis of d and l-homoalanine. Herein, we present the immobilization and use of this new immobilized biocatalyst under batch and continuous-flow conditions. The best optimized continuousflow condition allowed 89 % con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Besides these examples, there are still many more studies on the immobilization of lyases and applications in flow biocatalysis. In addition to selection of the appropriate enzyme and immobilization method according to the desired reaction, the coimmobilization of the required cofactors and the optimization of the conditions also need to be further investigated.…”
Section: Application Of Immobilized Lyases In a Flow Processmentioning
confidence: 99%
“…Besides these examples, there are still many more studies on the immobilization of lyases and applications in flow biocatalysis. In addition to selection of the appropriate enzyme and immobilization method according to the desired reaction, the coimmobilization of the required cofactors and the optimization of the conditions also need to be further investigated.…”
Section: Application Of Immobilized Lyases In a Flow Processmentioning
confidence: 99%
“…In addition to B. linens , MGL is also considered to be present in several strains grown on the surface of cheeses such as Micrococcus spp., Staphylococcus spp., and Arthrobacter spp. [ 77 ]. A review of the Arthrobacter strain and its ability to produce numerous enzymes have revealed the potential of this genus for the synthesis of MGL [ 78 , 79 ].…”
Section: Significance Of Arthrobacter Spp In the D...mentioning
confidence: 99%
“…A study on the enzymatic pathways of methionine degradation to methanethiol in Actinomycetes bacteria isolated from ripened cheese found that the Arthrobacter sp. strain produced MTL, DMDS, and DMTS from both methionine and α-keto-γ-(methylthio)-butyric acid (KMBA) by enzymatic conversion through one-step and two-step degradation pathways, respectively [ 77 ]. The possibility of the enzymatic degradation of methionine via both pathways is shown in Figure 1 In addition, the ability of smear cheese-ripening bacteria to produce VSC from methionine is possibly influenced by cysteine as it appears likely that part of methionine can be converted into cysteine by the transsulfuration pathway through two major enzymes, i.e., cystathionine γ-synthase (CGS) and cystathionine β-lyase (CBL) [ 81 ].…”
Section: Significance Of Arthrobacter Spp In the D...mentioning
confidence: 99%